Evidence that a deviation in the kynurenine pathway aggravates atherosclerotic disease in humans. (14th August 2020) - Baumgartner, R.; Berg, M.; Matic, L.; Polyzos, K. P.; Forteza, M. J.; Hjorth, S. A.; Schwartz, T. W.; Paulsson‐Berne, G.; Hansson, G. K.; Hedin, U.; Ketelhuth, D. F. J.
Abstract: Background: The metabolism of tryptophan (Trp) along the kynurenine pathway has been shown to carry strong immunoregulatory properties. Several experimental studies indicate that this pathway is a major regulator of vascular inflammation and influences atherogenesis. Knowledge of the role of this pathway in human atherosclerosis remains incomplete. Objectives: In this study, we performed a multiplatform analysis of tissue samples, in vitro and in vivo functional assays to elucidate the potential role of the kynurenine pathway in human atherosclerosis. Methods and results: Comparison of transcriptomic data from carotid plaques and control arteries revealed an upregulation of enzymes within the quinolinic branch of the kynurenine pathway in the disease state, whilst the branch leading to the formation of kynurenic acid (KynA) was downregulated. Further analyses indicated that local inflammatory responses are closely tied to the deviation of the kynurenine pathway in the vascular wall. Analysis of cerebrovascular symptomatic and asymptomatic carotid stenosis data showed that the downregulation of KynA branch enzymes and reduced KynA production were associated with an increased probability of patients to undergo surgery due to an unstable disease. In vitro, we showed that KynA‐mediated signalling through aryl hydrocarbon receptor (AhR) is a major regulator of human macrophage activation. Using a mouse model of peritoneal inflammation, we showed that KynA inhibits leukocyte recruitment. Conclusions: We have found that a deviation in the kynurenine pathway is associated with an increased probability of developing symptomatic unstable atherosclerotic disease. Our study suggests that KynA‐mediated signalling through AhR is an important mechanism involved in the regulation of vascular inflammation. Abstract :